Magnetic Colloidal Particles in Combinatorial Thin-Film Gradients for Magnetic Resonance Imaging and Hyperthermia - Sumera Khizar; Nasir Mahmood Ahmad; Hassan Saleem; Muhammad Asif Hamayun; Sadia Manzoor; Noureddine Lebaz; Abdelhamid Elaissari (Advances in Polymer Technology)
A stable oil-in-water (O/W) magnetic emulsion was prepared by the emulsification of organic ferrofluid in an aqueous media, and its theranostic applications were investigated. The synthesis and characterization of the organic ferrofluid were carried out comprising of superparamagnetic maghemite nanoparticles with oleic acid coating stabilized in octane. Both exhibit spherical morphology with a mean size of 6 nm and 200 nm, respectively, as determined by TEM. Thermogravimetric analysis was carried out to determine the chemical composition of the emulsion. The research work described here is novel and elaborates the fabrication of thin-film gradients with 5, 10, 15, and 20 bilayers by layer-by-layer technique using polydimethyl diallyl ammonium chloride (PDAC) and prepared magnetic colloidal particles. The thin-film gradients were characterized for their roughness, morphology, and wettability. The developed gradient films and colloids were explored in magnetic resonance imaging (MRI) and hyperthermia. T1- and T2-weighted images and their corresponding signal intensities were obtained at 1.5 T. A decreasing trend in signal intensities with an increase in nanoparticle concentration in colloids and along the gradient was observed in T2-weighted images. The hyperthermia capability was also evaluated by measuring temperature rise and calculating specific absorption rates (SAR). The SAR of the colloids at 259 kHz, 327 kHz, and 518 kHz were found to be 156 W/g, 255 W/g, and 336 W/g, respectively. The developed magnetic combinatorial thin-film gradients present a significant potential for the future efficient simultaneous diagnostic and therapeutic bioapplications.